Interactive structural color displays of nano-architectonic 1-dimensional block copolymer photonic crystals - Tae Hyun Park; Seunggun Yu; Jeongok Park; Cheolmin Park (Science and Technology of Advanced Materials)
For changing environmental circumstances, interactive structural color (SC) observation is a promising strategy to store and express external information. SCs based on self-assembled block copolymer (BCP) photonic crystals have been a research focus due to their facile and diverse nanostructures relying on the volume ratio of blocks. Their unique nano-architectonics can reflect incident light due to constructive interference of the two different dielectric constituents. Their excellent ability to change nano-architectonics in response to external stimuli (i.e. humidity, temperature, pH, and mechanical force) allows for a programmable and stimuli-interactive BCP SC display. In this review, recent advances in programmable and stimuli-interactive SC displays with the 1-dimensional self-assembled BCP nano-architectonics are comprehensively discussed. First, this review focuses on the development of programmable BCP SCs that can store various information. Second, stimuli-interactive BCP SCs capable of responding reversibly to external stimuli are also addressed. Particularly, reversible BCP SC changes are suitable for rewritable displays and emerging human-interactive BCP SC displays that detect various human information through changes in electric signals with the simultaneous alteration of the BCP SCs. Based on previously reported literature, the current challenges in this research field are further discussed, and the perspective for future development is presented in terms of material, nano-architectonics, and process.